Conscious Business Practices as a Driver of Reputational Capital in SMEs - Lorena RodrÍguez-Aldana, Marcia; Patricia López-Vázquez, Lilia; Rodríguez-Aceves, Lucía (Review of Business Management, 2024)
Purpose – The purpose of this study is to examine how reputational capital (RC) can be affected by the pillars of Conscious Capitalism as operationalized in conscious business practices (CBPs). Specifically, the practices were measured against four key tenets: higher purpose, stakeholder integration, conscious leadership, and conscious culture. Theoretical framework – RC, from the perspective of the resource-based view (RBV) theory, is considered a scarce and valuable resource that allows companies to achieve a competitive advantage. Specifically, businesses that stand out for their commitment to ethical and conscious business practices leverage their RC to gain legitimacy, credibility, and access to resources. Design/methodology/approach – This study adopted a post-positivist paradigm with a quantitative approach. Data were collected from small and medium-sized enterprises (SMEs) located in the western region of Mexico using an online survey. Using structural equation modeling, 115 valid responses were analyzed to test hypotheses derived from the proposed theoretical model. Findings – The RC of SMEs can be developed by declaring and operating according to a higher purpose and conscious culture. In this sample, stakeholder integration and conscious leadership did not directly impact RC. Originality/value – This study contributes to the literature on RC by exploring its development in SMEs in emerging economies. From a managerial perspective, it highlights the potential for SMEs to gain a competitive advantage by adopting CBPs and enhancing their RC.